Patterning of Metal Halide Perovskite Thin Films and Functional Layers for Optoelectronic Applications - Lee, Jin‑Wook; Kang, Seong Min (Nano-Micro Letters, 2023)
In recent years, metal halide perovskites have received significant attention as materials for next-generation optoelectronic devices owing to their excellent optoelectronic properties. The unprecedented rapid evolution in the device performance has been achieved by gaining an advanced understanding of the composition, crystal growth, and defect engineering of perovskites. As device performances approach their theoretical limits, effective optical management becomes essential for achieving higher efficiency. In this review, we discuss the status and perspectives of nano to micron-scale patterning methods for the optical management of perovskite optoelectronic devices. We initially discuss the importance of effective light harvesting and light outcoupling via optical management. Subsequently, the recent progress in various patterning/texturing techniques applied to perovskite optoelectronic devices is summarized by categorizing them into top-down and bottom-up methods. Finally, we discuss the perspectives of advanced patterning/texturing technologies for the development and commercialization of perovskite optoelectronic devices. Highlights: 1 This review discusses the status and perspectives of nano- to micron-scale patterning method for the optical management of perovskite optoelectronic devices. 2 We provide an overview of nanopatterning/texturing technologies for perovskites to achieve a high device performance and categorize them into top-down and bottom-up approaches.